2022
DOI: 10.1186/s12876-022-02516-2
|View full text |Cite
|
Sign up to set email alerts
|

The 30-day hospital readmission and mortality after surgery in colorectal cancer patients

Abstract: Purpose Hospital readmissions in the first weeks following surgery are common, expensive, and associated with increased mortality among colorectal cancer patients. This study is designed to assess the 30-day hospital readmission after colorectal cancer surgery and evaluate the risk factors that affect hospital readmission. Methods The study uses data from the Ministry of National Guard-Health Affairs Cancer Registry. All colorectal cancer patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The cohort’s small ROU and early discharge nevertheless appeared to produce low rates of readmission. In our study, 5% of patients were readmitted, which compares favorably to literature readmission rates that range from 7% to 25% 17–20 . Some older studies had previously identified early discharge as a significant risk factor for readmissions after colectomy 8,9 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The cohort’s small ROU and early discharge nevertheless appeared to produce low rates of readmission. In our study, 5% of patients were readmitted, which compares favorably to literature readmission rates that range from 7% to 25% 17–20 . Some older studies had previously identified early discharge as a significant risk factor for readmissions after colectomy 8,9 .…”
Section: Discussionsupporting
confidence: 81%
“…In our study, 5% of patients were readmitted, which compares favorably to literature readmission rates that range from 7% to 25%. [17][18][19][20] Some older studies had previously identified early discharge as a significant risk factor for readmissions after colectomy. 8,9 These studies, however, predated evolutions in robotic surgical technique and did not test a specific, tailored protocol for SDD.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 The impact of marital status on POC development varies among other cancer types; divorced or separated patients with oropharyngeal or laryngeal cancer have twice the odds of requiring readmission for complications but no association is seen amongst patients with colorectal cancer. 42,43 Yu et al noted that patients with breast cancer with government insurance, particularly Medicare, were also more likely to develop POC even after controlling for age and comorbidities. 44 Additional work is needed to determine the pathways between insurance, marital status, and POC.…”
Section: Discussionmentioning
confidence: 99%
“…Early postoperative hospital readmissions are also common, costly, and associated with increased mortality rates. [11][12][13] Research has shown that up to 27% of cancer patients discharged from hospitals are readmitted, 14 contributing to the healthcare burden in morbidity and mortality. 11 During the COVID-19 pandemic, most surgical procedures were performed for emergency or oncologic reasons to the detriment of the remaining elective procedures for benign conditions.…”
Section: Original Investigationmentioning
confidence: 99%
“…As a result, their QoL deteriorates from a lack of self-care knowledge and perspective on ostomy self-management. Early postoperative hospital readmissions are also common, costly, and associated with increased mortality rates 11–13 . Research has shown that up to 27% of cancer patients discharged from hospitals are readmitted, 14 contributing to the healthcare burden in morbidity and mortality 11 …”
Section: Introductionmentioning
confidence: 99%